Power and culture in emerging medical technology policymaking: the case of the human papillomavirus (HPV) vaccine in Canada. (1st June 2018) - Wyndham-West, Michelle; Wiktorowicz, Mary; Tsasis, Peter
Abstract : This article captures how scientific uncertainty is negotiated and its implications on public health policy. Through the case study of the Human Papillomavirus vaccine in Canada, we investigated how policymakers engage in 'sensemaking', the process whereby policymakers mediate shifting informational terrain to come to an understanding of what events and information mean, how they become significant and how they are acted upon. Key informant interviews reveal that policymakers make decisions amidst uncertainty by invoking public health cultural ideologies and by actively managing interactions with the manufacturer. This reflects a non-linear dispositif that is influenced by the co-production of culture and power.